150k views
3 votes
What is that answer

What is that answer-example-1
User Walter K
by
5.5k points

1 Answer

2 votes

(2^3)^4= (2^3)•(2^3)•(2^3)•(2^3) = (2•2•2)•(2•2•2)•(2•2•2)•(2•2•2)

(4^5)^2= (4^5)•(4^5) = (4•4•4•4•4)•(4•4•4•4•4)

(x^7)^3= (x^7)•(x^7)•(x^7) = (x•x•x•x•x•x•x)•(x•x•x•x•x•x•x)•(x•x•x•x•x•x•x)

(3•5)^3= (3•5)•(3•5)•(3•5)•(3•5) = (3•3•3•3)•(5•5•5•5)

(xy)^3= (xy)•(xy)•(xy)•(xy) = (xxxx)•(yyyy)

hope this helps :)


User Janvb
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.